2015
DOI: 10.14295/cs.v6i3.962
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic soil enzymes and their response to fertilization: a short review

Abstract: Enzymes are proteins that catalyze chemical reactions in living systems, transforming specific substrates into the products needed in biological cycles and for many edaphic processes. Soil enzymatic activities have been proposed as soil quality indicators, due to their relation with soil biology. Although the long-term effects of organic and mineral fertilization on physical and chemical soil properties have been previously studied, little is known about their effects on microbial community structure, microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…These results show that plant residue provides an increase in surface area of soil particles at that point which improve the association phosphatase to clay fraction in soil and decline the enzyme activity that hs been identified with the way that the activity of clay adsorbed enzyme is lower than free enzyme ;however, the utilization of walnut residues to soil encouraging microbial colonization because the plant residues manage soil moisture, temperature, aeration, pH, the carbon-nitrogen ratios in which ha vean important role for microbial activity, also enhanced availability nutrient also the P deficiency enhanced the activity of the phosphate from fungi and other microorganisms. These results agree with those that have been reported by 13 . They reported that the addition of organic residues can stimulate enzymatic activity as a result of microbial proliferation or enzymatic induction in response to the added residues.…”
Section: Resultssupporting
confidence: 94%
“…These results show that plant residue provides an increase in surface area of soil particles at that point which improve the association phosphatase to clay fraction in soil and decline the enzyme activity that hs been identified with the way that the activity of clay adsorbed enzyme is lower than free enzyme ;however, the utilization of walnut residues to soil encouraging microbial colonization because the plant residues manage soil moisture, temperature, aeration, pH, the carbon-nitrogen ratios in which ha vean important role for microbial activity, also enhanced availability nutrient also the P deficiency enhanced the activity of the phosphate from fungi and other microorganisms. These results agree with those that have been reported by 13 . They reported that the addition of organic residues can stimulate enzymatic activity as a result of microbial proliferation or enzymatic induction in response to the added residues.…”
Section: Resultssupporting
confidence: 94%
“…Indeed, key enzymes involved in microbial solubilization of P, alkaline phosphatases, were shown to be strongly decreased by P fertilization in the rhizosphere ( Spohn and Kuzyakov, 2013 ; Widdig et al, 2019 ) which suggests that fertilizer reduces hydrolytic enzyme-producing microorganisms or enzyme production in organisms capable of such function. The role of fertilization on soil enzymatic activities has been investigated in detail over the last 40 years ( Bautista-Cruz and Ortiz Hernandez, 2015 ) where increasing evidence suggests that chemical fertilization can inhibit or slow down synthesis of hydrolytic enzymes. However, linking enzyme production to individual microbiome members or groups is particularly challenging ( Sergaki et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clustering analyses of the hydrolases (Figure S2), oxidoreductases (Figure S3), or all enzymes abundance (Figure S4) confirmed the higher similarity of rehabilitating sites with native soils, such as observed in the soil bacteria taxonomic composition. Hydrolases (EC 3.-) and oxidoreductases (EC 1.-) are the most studied classes of enzymes when evaluating SOM transformation and nutrient cycling processes [26,27]. These transformations of SOM and nutrient cycling enable the assimilation of simple molecules by microorganisms and plants through the roots [28].…”
Section: Functional Similarity Of Enzymes Of Soil Organisms During Re...mentioning
confidence: 99%
“…Their abundances among the rehabilitation stages can be viewed in Figures S2-S4. Hydrolases (EC 3.-) and oxidoreductases (EC 1.-) are the most studied classes of enzymes when evaluating SOM transformation and nutrient cycling processes [26,27]. These transformations of SOM and nutrient cycling enable the assimilation of simple molecules by microorganisms and plants through the roots [28].…”
Section: Functional Similarity Of Enzymes Of Soil Organisms During Re...mentioning
confidence: 99%